Multiplicity of Positive Solutions for Fractional Differential Equation with p-Laplacian Boundary Value Problems - Sabbavarapu Nageswara Rao (International Journal of Differential Equations)
We investigate the existence of multiple positive solutions of fractional differential equations with p-Laplacian operator Da+β(ϕp(Da+αu(t)))=f(t,u(t)),  a<t<b, uja=0,  j=0,1,2,…,n-2, u(α1)(b)=ξu(α1)(η), ϕp(Da+αu(a))=0=Da+β1(ϕp(Da+αu(b))), where β∈(1,2], α∈(n-1,n],  n≥3, ξ∈(0,∞), η∈(a,b), β1∈(0,1], α1∈{1,2,…,α-2} is a fixed integer, and ϕp(s)=|s|p-2s,  p>1,  ϕp-1=ϕq,  (1/p)+(1/q)=1, by applying Leggett–Williams fixed point theorems and fixed point index theory.